1984
DOI: 10.1007/bf00501445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous prostaglandins on the release of leukotriene C4-like immunoreactivity and on coronary flow in indomethacin-treated anaphylactic guinea-pig hearts

Abstract: It is known that both vasoconstrictor cyclooxygenase products and sulfidopeptide-containing leukotrienes (LT) contribute to the biphasic coronary constriction observed in isolated perfused anaphylactic guinea-pig hearts. We have now investigated the effects of the cyclooxygenase inhibitor indomethacin and of several exogenous prostaglandins (PG) on the release of LTC4-like immunoreactivity and on various symptoms of cardiac anaphylaxis. Indomethacin decreased basal coronary flow and delayed the onset of corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1985
1985
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…The Table 5 Change in production and release ofcyclo-oxygenase products induced by leukotriene C4 (LTC4) or plateletactivating factor (Paf) in control and FPL 55712-pretreated hearts small inhibitory effect of indomethacin on the Pafinduced coronary vasoconstriction suggests that the predominant influence of cyclo-oxygenase metabolites is vasoconstrictor. In addition, indomethacin pretreatment failed to increase the release of either LTB4 or LTC4 in contrast to observations in guinea-pig cardiac (Aeringhaus et al, 1984) and pulmonary (Engineer et al, 1978) anaphylaxis. However, the release of leukotrienes from chopped lung induced by Paf (Beaubien et al, 1984) and that released from human lung parenchyma by Ca2" ionophore (Sautebin et al, 1985) has been found not to be enhanced by indomethacin pretreatment, suggesting that the enhancing effect of indomethacin may be stimulus-specific.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The Table 5 Change in production and release ofcyclo-oxygenase products induced by leukotriene C4 (LTC4) or plateletactivating factor (Paf) in control and FPL 55712-pretreated hearts small inhibitory effect of indomethacin on the Pafinduced coronary vasoconstriction suggests that the predominant influence of cyclo-oxygenase metabolites is vasoconstrictor. In addition, indomethacin pretreatment failed to increase the release of either LTB4 or LTC4 in contrast to observations in guinea-pig cardiac (Aeringhaus et al, 1984) and pulmonary (Engineer et al, 1978) anaphylaxis. However, the release of leukotrienes from chopped lung induced by Paf (Beaubien et al, 1984) and that released from human lung parenchyma by Ca2" ionophore (Sautebin et al, 1985) has been found not to be enhanced by indomethacin pretreatment, suggesting that the enhancing effect of indomethacin may be stimulus-specific.…”
Section: Discussioncontrasting
confidence: 71%
“…Thus, the PGF2., PGE2 and PGI2 released by Paf may reduce the Paf-induced coronary vasoconstriction. There is considerable evidence that the release of TXA2 in the coronary circulation leads to vasoconstriction (Anhut et al, 1978, Allan & Levi, 1981Aeringhaus et al, 1984). The Table 5 Change in production and release ofcyclo-oxygenase products induced by leukotriene C4 (LTC4) or plateletactivating factor (Paf) in control and FPL 55712-pretreated hearts small inhibitory effect of indomethacin on the Pafinduced coronary vasoconstriction suggests that the predominant influence of cyclo-oxygenase metabolites is vasoconstrictor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in apparent agreement with the previous observation that prostaglandin F2, (PGF2.) completely suppressed the antigen-induced arrhythmias while PGE2 and PGI2 decreased the incidence of arrhythmias in guinea-pig anaphylactic hearts (Aehringhaus et al, 1984). Thus, the enhancement in the anaphylactic release of LTC4 when sensitized hearts were challenged in the presence of indomethacin seen in the present experiments suggests two possibilities: firstly, cyclo-oxygenase products may exert a direct negative feedback on the anaphylactic release of leukotrienes and secondly, blocking the cyclo-oxygenase pathway resulted in a diversion of arachidonic acid metabolism away from cyclo-oxygenase towards the synthesis of lipoxygenase products.…”
Section: Discussionmentioning
confidence: 94%
“…Various mediators have been implicated in cardiac anaphylaxis. Technological advances during the past decade have revealed that lipoxygenation of arachidonic acid (AA) gives rise to a number of products with diverse biological activities and in particular, the discovery of leukotrienes as active constituents of SRS-A released immunologically from guinea-pig hearts (Aehringhaus et al, 1984) has enabled us to elucidate further the mediators involved in cardiac anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%